Impaired Performance on a Cognitively-Based Instrumental Activities of Daily Living Task, the 10-Item Weekly Calendar Planning Activity, in Individuals With Stroke Undergoing Acute Inpatient Rehabilitation - Jaywant, Abhishek; Arora, Catherine; Lussier, Alexis; Toglia, Joan (Frontiers in Neurology, 2021)
Performance-based, functionally relevant, and standardized measures of cognitive-instrumental activities of daily living (C-IADL) can complement neuropsychological tests of cognitive impairment and provide valuable clinical information to inform rehabilitation planning. Existing measures have been validated in the outpatient setting. Here, we sought to evaluate a 10-item, short-form of a C-IADL measure, Weekly Calendar Planning Activity (WCPA-10), in inpatients with stroke undergoing acute rehabilitation. The specific goal was to determine if the WCPA-10 could differentiate between stroke patients undergoing acute inpatient rehabilitation and healthy control individuals. We also explored whether the WCPA-10 would identify C-IADL limitations in stroke patients screened as having intact cognition. Seventy-seven stroke inpatients undergoing rehabilitation and 77 healthy control participants completed the WCPA-10, which involves entering a list of simulated, fictional appointments into a weekly schedule while keeping track of and adhering to multiple task rules and ignoring built-in obstacles and distractions. Compared to the control group, stroke patients had significantly worse accuracy, made more errors, used fewer cognitive strategies, followed fewer rules, took more time to complete the task, and were less efficient. 83% of stroke patients were less accurate than predicted by their age, and 64% used less strategies than their age prediction. Among 28 participants who screened as having “normal” cognitive function on the Montreal Cognitive Assessment, the majority had deficits on the WCPA-10. Our results provide initial support for use of a brief C-IADL assessment, WCPA-10, for individuals with stroke undergoing inpatient rehabilitation. They indicate that stroke patients have deficits in C-IADL accuracy, efficiency, and strategy use at this stage of stroke recovery. Results highlight the need to use performance based, functional cognitive assessments, even for those who perform well on cognitive screening tools.